Jesus of Nazareth: an independent historian's account of His life and teaching - Casey, Maurice (T&T Clark, 2010)
Professor Maurice Casey provides a sophisticated and engaging historical reconstruction of Jesus' life tackling controversial issues such as the Virgin Birth and the Resurrection. Casey's masterful treatment of the Aramaic sources and background to the Gospels make this volume unique in that no other life of Jesus has been written by a scholar with such expertise in the language which Jesus spoke, as a result Casey is able to draw us closer to the historical Jesus than ever before. Casey provides an up-to-date overview of the historical Jesus debate, covering the Jewishness of Jesus'